Validation of the Parent Behavior Inventory: A Confirmatory Factor Analysis - Merino-Soto, César (2004)
The Parental Behavior Inventory (PBI) it is a recent self-report instrument designed to capture two independent global dimensions of the parental behavior mothers/fathers of preschool and younger students: Two studies were made to obtain evidences of the construct validity and internal dependability. Our first study had the goal of verifying the two constructos (construct validity); the results obtained using an confirmatory factorial analysis point out that both constructs can be identified in the sample of Peruvian evaluated mothers (n=115). The reliability to both subscales also is satisfactory. The second study it was made in 58 mothers, and we looked for extend the construct validity by means of the correlacional study of the PBI with emotional, couple’s relationship and demographic variables; the results suppo